Assessment of Food Insecurity Among Marginal Farming Households in North Aceh Regency - Lukman Hakim; Mujiburrahmad; Cut Faradilla (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: North Aceh Regency’s average daily per-capita energy consumption is 1,927 kcal below the national adequacy standard placing it as the sixth-lowest in Aceh despite being the province’s largest rice producer. Limited resources reduce the purchasing power of marginal farming households, diminishing their food availability and consumption. These households represent a relevant sample for developing effective food-security solutions, as their high vulnerability makes them suitable for testing new agricultural methods amid climate-related challenges.Purpose: This study aimed to determine the categories and composite mapping of food insecurity among marginal rice farming households in North Aceh Regency, Aceh Province, Indonesia.Design/methodology/approach: The Household Food Insecurity Access Scale (HFIAS) and Household Food Insecurity Access Prevalence (HFIAP) instruments were employed to identify and analyze vulnerability instruments and priority composite mapping. Both quantitative and qualitative analytical techniques were used, in alignment with the research objectives. Marginal rice farmers from four villages across two sub-districts were selected via purposive sampling complemented by proportional random sampling, yielding a sample of 100 households from four villages in North Aceh Regency.Findings/Results: The results revealed that 43% of marginal rice‑farming households were classified as moderately food‑insecure, 35% as severely food‑insecure, and 22% as slightly food‑insecure. Furthermore, FSVA-based mapping designated Lhok Kareung Village and Nga Lt Village in Lhoksukon District as Priority Composite 1, with a vulnerability index of 0.23%, denoting severe food insecurity.Conclusion: The results of the study indicate that most marginal rice‑farming households in North Aceh Regency were classified as moderately food‑insecure (43%), while the remainder were categorized as severely and slightly food‑insecure, with percentage values of 35% and 22%, respectively. Consequently, these findings elucidate the food security level of marginal farmers in North Aceh, which has direct implications for managers focusing on availability, access, including affordability of food distribution, and utilization, thereby fostering a sustainable food system. Effective managerial implications can foster food-secure marginal farmers, indicated by infrastructural modernization (provision of warehousing for stock and accessibility, precise irrigation, food diversification, affordable prices, and enhanced welfare reflected in higher incomes), as well as community cultural factors grounded in local wisdom.Originality/value (State of the art): This study first analyzes the integration of food‑insecurity analysis with food‑security composite mapping, providing a nuanced understanding of vulnerability dynamics. Keywords: food insecurity, marginal farming households, fsva instrument, food security priority map